The Effect of Ergonomic Gymnastics on Joint Pain in Community-Dwelling Elderly - Martha Lowrani Siagian; Anggi Hanafiah Syarif; Andreas Wojtyla Sukur; Beatric Maria Dwijayanti Baga; Ni Ketut Emi Rayuni (Jurnal Ners, 2019)
Background: The aging process that occurs in the elderly is characterized by a decreasing immune system and physical impairment. The most common complaint is joint pain. The aim was to determine the effect of ergonomic gymnastics on the elderly who experienced joint pain.Method: The samples totaled 110 respondents who had joint pain at Krembangan-Surabaya obtained through the total sampling technique. The data was collected through observation sheets with one group pre-post-test design, and it was analyzed through the Wilcoxon text. The result showed that after 9 sessions of 60 minutes each for two months found that ergonomic gymnastics could influence the reduction of joint pain with a significance level of 0.00 (p<0.05).Discussion: There were a decreasing number of respondents that felt moderate pain (82 to 44) and this automatically meant that there was an increasing number of mild pain respondents (28 to 66).Conclusion: Exercising regularly and with the correct methods could provide an excellent benefit to maintain bodily health, especially to reduce joint pain in the elderly. It is expected that all health care providers in primary health services or in a private clinics should know and be able to conduct ergonomic gymnastics using the correct methods.